Global production networks, regional development trajectories and smallholder livelihoods in the Global South. (26th December 2018) - Vicol, Mark; Fold, Niels; Pritchard, Bill; Neilson, Jeffrey
Abstract: Recent advances in global production network theory, known as GPN 2.0, provide a theoretically sophisticated framework for understanding the articulation of global production systems with regional development trajectories. However, this framework was largely derived from lessons out of empirical analyses of the strategic coupling and value capture trajectories of firms in certain manufacturing and service sector 'hot spots', primarily in East and Southeast Asia, and its wider applicability for other contexts remains uncertain. This paper aims to address this lacuna by examining the potential for GPN 2.0 to understand regional development trajectories in agricultural production landscapes in the Global South dominated by smallholder-based farms that generate outputs for national and international markets. The distinctive characteristics of smallholders throw up significant challenges for the explanatory applicability of GPN 2.0 for rural development, at least as it has been developed so far. A key challenge is that smallholders cannot be considered equivalent to 'firms' as conceived in GPN 2.0. To overcome this problem, this paper argues for bringing a livelihoods perspective to bear on GPN 2.0. We illustrate the usefulness of this approach through reference to a case study of potato contract farming in Maharastra, India.